Benedetto Pamphilj in Bologna (1690–3): Documents on his Patronage of Music. Issue 1 (2016) - van der Linden, Huub
Abstract : Between 1690 and 1693 Cardinal Benedetto Pamphilj (1653–1730) held the office of Cardinal-Legate of Bologna. Although he is well known as a patron of music in seventeenth- and eighteenth-century Rome, his time in Bologna has received virtually no attention. This article provides an extensive overview of these years on the basis of a large body of previously unpublished documents. Three appendices provide transcriptions of 74 documents from the cardinal's financial administration, 44 excerpts from a Bolognese institutional diary and a chronology of events involving the cardinal.